Ninety-Six Distinct Real Matrices for Representing a Quaternion Number - W. E. Ahmed (Journal of Mathematics)
In this paper, we investigate on the number of all possible real matrices representing a quaternion number as three 4×4 skew-symmetric matrices plus the identity matrix of order 4, and how to determine these matrices. We establish that there are 96 distinct real matrices having this property, and by matrix row operations, we obtain these matrices.